2015
DOI: 10.31018/jans.v7i1.591
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient management for jute-rice cropping system using soil test target yield equation

Abstract: A field experiment was conducted during the year 2011-13 to study the nutrient management based on soil test to achieve the target yield of jute and rice and their effect of soil nutrient status for jute-rice cropping system. The target yield of jute fibre (3.5 t/ha) with -6% deviation and target yield of rice (5.5 t/ha) were achieved with application of 100% NPK based on ST-TY based along with 5 t/ha Farm Yard Manure (FYM). The highest system productivity (11.7 t/ha) and benefit-cost ratio (3.16) was also rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
3
1
0
Order By: Relevance
“…ramie compost in course of time. The results are in conformity with the earlier research findings in jute (Majumdar et al, 2014), roselle (Saha et al, 2008) and juterice cropping system (Singh et al, 2015). The available phosphorus content of soil in the INM treated plots were statistically at par with that of plots receiving inorganic nitrogen at 150% N application level (Table 4).…”
Section: Soil Fertility Statussupporting
confidence: 91%
See 2 more Smart Citations
“…ramie compost in course of time. The results are in conformity with the earlier research findings in jute (Majumdar et al, 2014), roselle (Saha et al, 2008) and juterice cropping system (Singh et al, 2015). The available phosphorus content of soil in the INM treated plots were statistically at par with that of plots receiving inorganic nitrogen at 150% N application level (Table 4).…”
Section: Soil Fertility Statussupporting
confidence: 91%
“…Moreover, the higher K content in ramie compost possibly had increased the availability of potassium in soil and facilitated its uptake by the crop. Similar increase in phosphorus and potassium uptake due to integrated nutrient management had also been reported in jute (Mitra et al, 2010), roselle (Saha et al, 2008), wheat (Mitra et al, 2006) and in jute-rice cropping system (Singh et al, 2015). The nutrient uptake by ramie was found to be more at higher (150%) nitrogen supply level with both inorganic and INM treatments in all the years of experimentation.…”
Section: Nutrient Uptakesupporting
confidence: 77%
See 1 more Smart Citation
“…Highest B:C ratio was recorded in STCR 20 q ha -1 (5.45) followed by STCR 15 q ha -1 (4.32). So STCR treated field performed best overall viz., higher yield, net benefits and B:C ratio compare to others treated field due to balanced supply of nutrients from fertilizer, efficient utilization of applied fertilizer nutrients in the presence of organic sources and the synergistic as well as beneficial effect of the conjoint addition of several sources of nutrients (Singh, 2019 andSingh et al, 2017). Post-harvest soil values revealed that a sufficient build up and maintenance of SN, SP and SK are found under STCR study compare to farmer practices and general recommended dose.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the experiment showed that when NPK and FYM were administered together, jute crop nutrient uptake and soil nutrient status were at their maximum, even three years later. Inorganic and organic fertilizer used in combination (FYM) produced the desired yield while maintaining the fertility of the soil (Singh et al, 2015). When fertilizers are provided in an integrated manner, the jute crop absorbs far more of them.…”
Section: Outcome Of Prior Inm In Jute Researchmentioning
confidence: 99%